Endothelial‐derived von Willebrand factor accelerates fibrin clotting within engineered microvessels. (11th April 2022) - Rayner, Samuel G.; Scholl, Zackary; Mandrycky, Christian J.; Chen, Junmei; LaValley, Karina N.; Leary, Peter J.; Altemeier, William A.; Liles, W. Conrad; Chung, Dominic W.; López, José A.; Fu, Hongxia; Zheng, Ying
Abstract: Background: Von Willebrand factor (VWF) is classically associated with primary hemostasis and platelet‐rich arterial thromboses, but recently has also been implicated in fibrin clotting and venous thrombosis. Direct interaction between fibrin and VWF may mediate these processes, although prior reports are conflicting. Objectives: We combined two complementary platforms to characterize VWF‐fibrin(ogen) interactions and identify their potential physiologic significance. Methods: Engineered microvessels were lined with human endothelial cells, cultured under flow, and activated to release VWF and form transluminal VWF fibers. Fibrinogen, fibrin monomers, or polymerizing fibrin were then perfused, and interactions with VWF evaluated. Thrombin and fibrinogen were perfused into living versus paraformeldahyde‐fixed microvessels and the pressure drop across microvessels monitored. Separately, protein binding to tethered VWF was assessed on a single‐molecule level using total internal reflection fluorescence (TIRF) microscopy. Results: Within microvessels, VWF fibers colocalized with polymerizing fibrin, but not fibrinogen. TIRF microscopy showed no colocalization between VWF and fibrinogen or fibrin monomers in a microfluidic flow chamber across a range of shear rates and protein concentrations. Thrombin‐mediated fibrin polymerization within living microvessels triggered endothelial VWF release, increasing the rate and amount of microvessel obstruction compared to fixed vessels with an inert endothelium. Conclusions: We did not identify specific binding between fibrin(ogen) and VWF at a single‐molecule level. Despite this, our results suggest that rapid release of endothelial VWF during clotting may provide a physical support for fibrin polymerization and accelerate thrombosis. This interaction may be of fundamental importance for the understanding and treatment of human thrombotic disease.